Perancangan PERANCANGAN DAN IMPLEMENTASI OPTIMALISASI PENDATAAN WARGA BARU DI PERUMAHAN BERBASIS ANDROID - Dwi Saputra, Kevin; Sitohang, Sunarsan (JURNAL ILMIAH INFORMATIKA, 2024)
In this era, technological development is growing rapidly. Android is one of the operating systems currently available. The use of this operating system is very popular for cellphone development companies today. Rt 01 is in the Rw 01 area of ​​Muka Kuning Indah II Housing, Batu Aji District, Batam City. In the process of processing documents, residents currently still use traditional methods. Using this traditional method can cause problems, such as data that can be lost and data damage that can occur. One example is managing data on new residents who move to this RT. New citizen data is recorded in a book, as a temporary data storage place before being transferred to Excel. Creating an Android application to help make data collection easier for new residents is a good breakthrough. The results of this research are in the form of an Android application for RT 01 to register new residents, as well as helping to facilitate processing of other documents